Micro and nanoplastics ravaging our agroecosystem: A review of occurrence, fate, ecological impacts, detection, remediation, and prospects - Emmanuel Sunday Okeke; Kingsley Ikechukwu Chukwudozie; Charles Izuma Addey; Joseph Onyekwere Okoro; Timothy Prince Chidike Ezeorba; Edidiong Okokon Atakpa; Charles Obinwanne Okoye; Charles Ogugua Nwuche (Heliyon, 2023)
Micro-and nanoplastics (MNPs) are particles that are smaller than a millimeter in size and have infiltrated both terrestrial and aquatic ecosystems. MNPs pollution have become a widespread problem causing severe adverse effects on human health and the environment worldwide. Once in the environment, these polymers are not easily degradable due to their recalcitrant nature and small size and are easily consumed by aquatic organisms and transported through the food chain, at great risk to human health. Substantial evidence demonstrates the negative effects of MNPs residues on aquatic organisms' reproductive and developmental defects. Similarly, soil flora, soil quality, and plant height have been severely impacted by their presence in the agroecosystem. This is evident in the inhibition of water absorption by blocked seed pores, delayed germination, and the dramatic decline in transpiration rates and growth of plant roots, inevitably leading to drop in biomass and crop production, posing an overall threat to global food security. In this review, we present the impact of MNPs in agroecosystems around the globe, including their sources, occurrence, distribution, transport, and ultimate fate. We recommend using bio-based plastics, eco-friendly remediation strategies, reformed agricultural practices, non-single-use synthetic plastic legislation, and increased plastic waste disposal awareness campaigns as effective tools to mitigate this problem.